(untitled) (Research, Society and Development, 2021)
Background and objective: The systematic review of studies that deal with the self-care of women undergoing mastectomy is crucial to assess the safety and effectiveness of care interventions provided to this portion of the population. The purpose of this article is to present a tutorial for planning and executing systematic reviews in a cohesive way, following a dynamic, team-based workflow. Methods: A systematic literature review is the type of research that organizes, critiques and integrates the evidence available in the literature. The information disclosed in articles is not always free from bias, and to minimize these interferences it is necessary that a literature review includes items such as design, protocol registration, execution, analysis of results and wide dissemination. To maintain cohesion about systematic reviews, researchers have increasingly used the PRISMA flowchart, which has improved the quality of reports from systematic reviews, as it provides a list of items to be described, and this article emphasizes the main steps for carrying out a systematic review. Final considerations: The scientific evidence obtained through a well-designed systematic literature review can provide the health professional with greater confidence at the time of clinical practice, improve the benefits to assisted patients and serve as a tool to assist managers, it can also corroborate to the implementation of new strategies in favor of general health.